2007
DOI: 10.1176/appi.ajp.2007.06101639
|View full text |Cite
|
Sign up to set email alerts
|

Risk of Recurrence in Women With Bipolar Disorder During Pregnancy: Prospective Study of Mood Stabilizer Discontinuation

Abstract: Discontinuation of mood stabilizer, particularly abruptly, during pregnancy carries a high risk for new morbidity in women with bipolar disorder, especially for early depressive and dysphoric states. However, this risk is reduced markedly by continued mood stabilizer treatment. Treatment planning for pregnant women with bipolar disorder should consider not only the relative risks of fetal exposure to mood stabilizers but also the high risk of recurrence and morbidity associated with stopping maintenance mood s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

9
284
1
7

Year Published

2009
2009
2018
2018

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 508 publications
(301 citation statements)
references
References 48 publications
9
284
1
7
Order By: Relevance
“…Information regarding potential teratogenic effects of different psychotropic medications, as well as limitations of the scientific evidence, should be discussed and carefully considered. The decision to stop medications pre‐conceptually should ideally occur only after careful individualized risk‐benefit analysis for a given patient 511, 512, 513. If pharmacotherapy is required, monotherapy at minimum effective dose is recommended whenever possible 514, 515…”
Section: Specific Populationsmentioning
confidence: 99%
See 1 more Smart Citation
“…Information regarding potential teratogenic effects of different psychotropic medications, as well as limitations of the scientific evidence, should be discussed and carefully considered. The decision to stop medications pre‐conceptually should ideally occur only after careful individualized risk‐benefit analysis for a given patient 511, 512, 513. If pharmacotherapy is required, monotherapy at minimum effective dose is recommended whenever possible 514, 515…”
Section: Specific Populationsmentioning
confidence: 99%
“…A longitudinal study conducted in a tertiary care centre found a high risk of recurrence during pregnancy: 85% of pregnant women with BD who discontinued a mood stabilizer and 37% of those who were maintained on one or more mood stabilizers experienced a mood episode—predominately depressive or mixed—during pregnancy. For nearly half of the patients, recurrence occurred in the first trimester, with the median time for recurrence for those abruptly discontinuing treatment being 2 weeks, compared to 22 weeks for those who were gradually tapered off 511. However, studies from primary care, as well as obstetric centres, found low rates of relapse or hospitalizations in pregnancy 526…”
Section: Specific Populationsmentioning
confidence: 99%
“…In particular, the reported reoccurrence rates for bipolar disorder are approaching 50% in the antenatal period and 70% in the postnatal period (Viguera et al, 2007). Women with a diagnosis of schizophrenia are at an increased risk of psychosis (Munk-Olsen et al, 2006, Munk-Olsen et al, 2009, whilst women with a history of depression are also at an increased risk of its recurrence, continuation, or exacerbation (Bennet, 2004).…”
Section: Introductionmentioning
confidence: 99%
“…Considerable clinical and research attention has been devoted to documenting both the prevalence of perinatal depression and risk factors for its emergence during the perinatal period. [1][2][3][4] However, much less is known about psychiatric comorbidity in women with perinatal depression. The current study addressed the prevalence of comorbid eating disorders (ED) in these women.…”
Section: Introductionmentioning
confidence: 99%